Aiding AIDS Through Writing: A Study and Bibliography - Emily Nye (Journal of the Assembly for Expanded Perspectives on Learning, 1996)
A writing group at an HIV clinic generated four kinds of narratives, each with a different healing function. A selected bibliography follows.